Whole exome sequencing identifies a new mutation in the SLC19A2 gene leading to thiamine‐responsive megaloblastic anemia in an Egyptian family. Issue 7 (29th May 2019) - Amr, Khalda; Pawlikowska, Patrycja; Aoufouchi, Said; Rosselli, Filippo; El‐Kamah, Ghada
Abstract: Background: The Solute Carrier Family 19 Member 2 ( SLC19A2, OMIM *603941) encodes the thiamine transporter 1 (THTR‐1) that brings thiamine (Vitamin B1) into cells. THTR‐1 is the only thiamine transporter expressed in bone marrow, cochlear, and pancreatic beta cells. THTR‐1 loss‐of‐function leads to the rare recessive genetic disease Thiamine‐Responsive Megaloblastic Anemia (TRMA, OMIM #249270). Methods: In vitro stimulated blood lymphocytes were used for cytogenetics and the isolation of genomic DNA used to perform whole exome sequencing (WES). To validate identified mutations, direct Sanger sequencing was performed following PCR amplification. Results: A 6‐year‐old male born from a consanguineous couple presenting bone marrow failure and microcephaly was referred to our clinic for disease diagnosis. The patient presented a normal karyotype and no chromosomal fragility in response to DNA damage. WES analysis led to the identification of a new pathogenic variant in the SLC19A2 gene (c.596C>G, pSer199Ter) allowing to identify the young boy as a TRMA patient. Conclusion: Our analysis extend the number of inactivating mutations in SLC19A2 leading to TRMA that could guide future prenatal diagnosis for the family and follow‐up for patients. Abstract : We reported here the identification of a new stop‐codon variant in an Egyptian patient initailly examined for Fanconi anemia suspection and finally diagnosed as TRMA following whole exome sequencing.